The influence of accounting information systems, internal control systems and human resource competencies on the quality of financial reports with regional government leadership style as a moderation variable (Case study of regency/city regional government in North Sulawesi Province) - Anggraini, Agittashela; Kalangi, Lintje; Warongan, Jessy D. L. (Yayasan Widyantara Nawasena Raharja, 2024)
The purpose of this research is to examine the relationship between the quality of financial statements and factors such as accounting information systems, internal control systems, and human resource competencies. The study will use district and city local governments in North Sulawesi province as a case study to examine this relationship, with leadership styles in local governments serving as moderating variables. Using a sample of 170 respondents in the year 2024, this study draws on primary sources to examine all the local governments in North Sulawesi Province. Multiple linear regression analysis is employed for the analysis. Accounting information systems, HR competencies, and internal control systems all positively affect financial report quality, according to multiple linear regression testing. Leadership styles moderate the effect of ICS on report quality. This means that competent human resources, an effective internal control system, and an accounting information system all contribute to higher-quality financial reports, and that a leadership style in local government that links a solid control system to strong financial reporting is also important. Accounting information systems and human resource capabilities are negatively impacted by leadership styles in local governments, according to this study. Leadership style has little effect on accounting information systems and human resource capabilities in terms of producing high-quality financial reports, according to the study's implications. There is no statistical evidence that a leader's style can influence the accuracy of financial reports, even while it moderates the accounting information system and HR competencies. Superior financial reporting is more likely to result from a management style that keeps the internal control system in check.